Poor Mobilization in T-Cell-Deficient Nude Mice is Explained by Defective Activation of Granulocytes and Monocytes. Issue 1 (January 2017) - Wysoczynski, Marcin; Adamiak, Mateusz; Suszynska, Malwina; Abdel-Latif, Ahmed; Ratajczak, Janina; Ratajczak, Mariusz Z.
It has been reported that both SCID mice and SCID patients poorly mobilize hematopoietic stem/progenitor cells (HSPCs) in response to granulocyte colony-stimulating factor (G-CSF). This defect has been proposed to result from a lack of naturally occurring IgM immunoglobulins to trigger activation of the complement cascade (ComC) and release of C5 cleavage fragments crucial in the mobilization process. However, SCID individuals also have T-cell deficiency, and T cells have been shown to modulate trafficking of HSPCs. To learn more about the role of T lymphocytes, we performed mobilization studies in T-lymphocyte-deficient nude mice and found that these mice respond poorly to G-CSF and zymosan but are normal mobilizers in response to AMD3100. Since nude mice have normal levels of IgM immunoglobulins in peripheral blood and may activate the ComC, we focused on the potential involvement of Gr1 + granulocytes and monocytes, which show defective maturation in these animals. Using a nude mouse mobilization model, we found further support for the proposition that proper function of Gr1 + cells is crucial for optimal mobilization of HSPCs.